The Effect of Providing Animated Video Education on Premarital Knowledge About Stunting Prevention - Katarina, Yusran; Rahman, Hardianti; Andriwati, Andi Bau (Gema Wiralodra, 2025)
According to The South Sulawesi Provincial Health Office reported that the stunting rate decreased from 27.3% in 2023 to 23.3% in 2024. The target for reducing stunting in South Sulawesi Province is 6.1% in 2045. The government's target is to reduce the national stunting rate to 18.8% in 2025, 14.2% in 2029, and 5% in 2045, which means it has not yet reached the target.StuntingStunting is a condition of stunting in toddlers due to chronic malnutrition, resulting in the child being too short for their age. The period from 0-24 months of age is a crucial period for a child's quality of life, and is therefore often referred to as the golden period. Prospective brides and grooms are also prospective parents, so providing education on stunting prevention through animated videos is crucial. This type of research is...Cross Sectional .Study Cross Sectional with designpost test design with a population of 105 people and a sample of 51 people. The results of the study showed that the mean value before and after treatment decreased, wherepre testis 2.25 while the valuepost testis 1.27 reinforced with the Sig. value. (2-tailed) of 0.000, which indicates that there is an influence of providing animated videos about preventing stunting on the knowledge of prospective brides and grooms about preventing stunting.